FIREWOOD QUALITY OF Eucalyptus spp. CLONES FOR AGROINDUSTRY SUPPLY IN MATO GROSSO, BRAZIL - Vinicius Trombini Jambers; Camila Nunes Amorim; Camila Mendes Campos; Leonardo Lopes da Rocha; Angélica de Cassia Oliveira Carneiro; Ana Márcia Macedo Ladeira Carvalho; Aylson Costa Oliveira; Bárbara Luísa Corradi Pereira (Revista Árvore)
ABSTRACT The use of renewable energy sources from biomass has been increasing in the agricultural sector, with a focus on wood produced from eucalyptus plantations. Given the economic significance of the state of Mato Grosso, Brazil, this study aimed to evaluate the energy potential of different eucalyptus clones planted in the state, with an emphasis on their use in agroindustry. Three trees were selected from each of eleven different eight-year-old genetic materials in a clonal test located in Tangará da Serra, MT. The bark percentage, basic density, higher heating value, and both elemental and structural chemical composition of the wood were determined. A cluster analysis was then performed. Additionally, a case study was conducted considering firewood consumption and costs for drying corn and soybeans. The bark percentage ranged from 5.00 to 11.04%. Basic density varied from 478 to 588 kg.m-3, with significant differences among the three groups formed; the best-performing clones had values approximately 6% higher than the others. Higher heating values ranged from 4,609.33 to 4,743.67 kcal.kg-1. Total lignin content also varied between clones, with one group standing out by ranging from 27.81% to 29.76%. Total extractive content ranged from 3.72 to 7.76%. The average energy density was 2.50 Gcal.m-3, with no significant differences between the clones. Cluster analysis identified two main groups. The evaluated eucalyptus clones showed satisfactory characteristics for energy use, with clones 1, 4, and 10 standing out. The use of eucalyptus clones with superior energy properties can reduce wood consumption for drying grains such as soy and corn by up to 20%.